The right to scientific discovery as an object of legal protection: National and international perspectives - Kotenko, Mykola; Dzisiak, Oleg; Tymoshenko, Olga; Zozulya, Evgeniy; Ivanchenko, Eduard (Universitas Ahmad Dahlan, 2024)
Introduction to the Problem: This article explores the concept of the right to scientific discovery as a fundamental aspect of human rights, examining its legal protection both at the national and international levels. Purpose/Study Objectives: The purpose of this research is to analyze the domestic legal framework for rights to scientific discoveries and characterize foreign approaches to regulating relations related to the implementation and protection of rights to this object of intellectual property. Design/Methodology/Approach: The methodology covers both general scientific and specific legal methods. In particular, the authors used the following methods: analysis and synthesis, formal-legal, comparative-legal, analytical-prognostic, socio-legal research, empirical, and induction methods. By analyzing national laws, international treaties, and case studies, this research provides a comprehensive overview of the legal landscape surrounding the right to scientific discovery. Findings: The right to scientific discovery is a critical aspect of legal protection at both national and international levels. While intellectual property laws provide a primary mechanism for protecting scientific discoveries, broader human rights frameworks and international treaties also play vital roles. Moreover, significant disparities exist between countries regarding access to scientific knowledge and research capacity. Thus, international cooperation and support are crucial to mitigate these imbalances and promote global equity in scientific advancement. Finally, balancing the rights of individual inventors with the public interest, ethical considerations, and global equity remains a complex and ongoing challenge. Paper Type: Research Article